Home Industry Assistance Upgrades Sambel Pecel Mbak Nur’s Production Capacity and Product Quality - Dwi Ishartani; Setyaningrum Ariviani; Siswanti Siswanti; Gusti Fauza; Dimas Rahadian Aji Muhammad; Windi Atmaka (Universitas Sebelas Maret, 2025)
Sambel pecel home industry, founded by Tri Nurhayati, sells sambel pecel (pecel sauce) products under the brand “Sambel Pecel Mbak Nur